2017
DOI: 10.1097/brs.0000000000002308
|View full text |Cite
|
Sign up to set email alerts
|

Laminoplasty Does not Lead to Worsening Axial Neck Pain in the Properly Selected Patient With Cervical Myelopathy

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…Many studies on pain after laminoplasty focus on axial neck pain, which negatively affects clinical outcomes [22][23][24][25][26][27]. Our study extended these results, clarifying that neck or shoulder pain is an indicator of poor results for cervical function, such as the movements involved in drinking or looking up or down [10].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Many studies on pain after laminoplasty focus on axial neck pain, which negatively affects clinical outcomes [22][23][24][25][26][27]. Our study extended these results, clarifying that neck or shoulder pain is an indicator of poor results for cervical function, such as the movements involved in drinking or looking up or down [10].…”
Section: Discussionsupporting
confidence: 75%
“…In particular, pain in the arms or hands directly degraded the QOL. These results specifically emphasize the importance of perioperative and postoperative pain management [25,26,28,29]. To reduce pain, for example, it might be better to select laminectomy and fusion surgery over laminoplasty for patients with axial pain or a kyphotic preoperative C2-C7 alignment [26].…”
Section: Discussionmentioning
confidence: 94%
“…After intraoperative xation with lateral mass screws, the trend of progressive cervical curvature loss and high frequency of kyphosis deformities were effectively controlled, but the cervical curvature became smaller in some patients still existence [3,5]. From the analysis on anatomy and biomechanics, both open-door laminoplasty and laminectomy will destroy the spinous process, vertebral plate and posterior ligaments complex to varying degrees, resulting in loss of effective attachment points of the cervical posterior muscle group, weakening of the muscle tension band, loss or straightenness of curvature due to the failure to maintain the original cervical curvature [4,6,9,[11][12]. It has been reported that maintaining a good physiological curvature can make cervical spine more elastic, relieve shock and buffer stress during movement, and play a role in protecting the spinal cord [7].…”
Section: Discussionmentioning
confidence: 99%
“…Neurological recovery rate= (postoperative score -preoperative score)/ (17 -preoperative score) × 100%. Axial symptoms (AS) are often manifested as postoperative neck pain with neck and shoulder stiffness, tension, and discomfort of sore and swollen [9]. According to the evaluation criteria developed by Hosono et al [10].…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…The Neck Disability Index (NDI), first introduced by Vernon et al in 1991, 55 has been widely translated, repeatedly validated, and extensively used for measurement of pain and functional outcome in the cervical spine. 31,38,47,[56][57][58][59][60][61][62] Similarly, the introduction of the Japanese Orthopaedic Association (JOA) myelopathy scale, 63 and its subsequent adaptation into the modified JOA (mJOA) to fit the North American context, 64 has been instrumental in studies of degenerative cervical myelopathy. 31,35,38,47,62,65,66 The entire list of outcome measures for spine surgery is extensive, and categorically includes measures aimed at various aspects of care as well as particular populations.…”
Section: Reporting Of Outcomesmentioning
confidence: 99%